Impact of intercropping on agronomic and metabolic responses of Medicago sativa and Hordeum marinum under nutrient deficiency and drought stress - Guerchi, Amal; Mnafgui, Wiem; Garijo, Gustavo; Mahjoub, Asma; Ludidi, Ndiko; Gonzalez, Esther M.; Badri, Mounawer (Frontiers in Agronomy, 2025)
IntroductionIntercropping has emerged as a promising strategy to enhance crop performance and resilience under conditions of abiotic stress. Medicago sativa and Hordeum marinum constitute a potentially complementary forage system for semi-arid regions, yet their integrated physiological and metabolic responses to combined water and nutrient limitations remain poorly characterized. This study evaluated whether intercropping could improve productivity, nutrient acquisition, and biochemical stress adaptation under drought and reduced fertilization.MethodsA controlled greenhouse experiment was conducted to compare monocropping and intercropping systems of M. sativa and H. marinum under drought (40% field capacity) and three fertilization regimes (0%, 50%, and 100% of nutrient demand). Plants were harvested at three successive growth stages. Biomass production, mineral ion profiles (Na⁺, Ca²⁺, Cl⁻, NO₃⁻), and metabolite signatures: including carbohydrates, organic acids, and amino acids, were quantified to assess stress responses and resource-use efficiency.ResultsBiomass production was significantly influenced by cultivation system, fertilization level, and their interaction, with intercropping consistently enhancing productivity across all harvests. Ion profiling revealed distinct nutrient redistribution in intercropped plants, particularly in H. marinum, which accumulated higher Cl⁻ and NO₃⁻ in leaves and greater Ca²⁺ and Na⁺ in roots. Metabolomic analyses showed that intercropping under nutrient deficiency promoted the accumulation of stress-mitigating metabolites, including raffinose, fructose, sucrose, citric acid, succinic acid, oxalic acid, proline, GABA, and glutamine, reflecting improved osmotic regulation and energy metabolism.DiscussionThe integrative physiological and biochemical adjustments induced by intercropping resulted in enhanced nutrient uptake, stronger osmotic balance, and more efficient metabolic functioning under stress. These synergistic responses explain the superior biomass performance and resilience of both species under drought and low fertilization. Intercropping M. sativa with H. marinum thus represents a robust, low-input strategy for sustainable forage production in semi-arid environments.